RELATIONSHIP BETWEEN AUDIT COMMITTEE CHARACTERISTICS, EXTERNAL AUDITORS AND ECONOMIC VALUE ADDED (EVA) OF PUBLIC LISTED FIRMS IN MALAYSIA - Abdullah, Al Mamun; Qaiser Rafique, Yasser; Md. Ashikur, Rahman; Wickramasinghe, Ananda; Nathan, Thurai Murugan (Virtus Interpress, 2014)
Malaysia is a developing economy which is one of the corporate leaders in South East Asian countries. Practicing audit committee is mandatory for public listed firms in Malaysia according to Bursa Malaysia Listing Requirements as well Malaysian Code of Corporate Governance. The purpose of this paper is to examine the association between audit committee characteristics and firm performance among public listed firms in Malaysia. This study employed EVA as performance measurement tool. The sample is 75 firm year observations and covers fiscal years 2008-2010. The study found that audit committee independence is positively associated with firm performance while audit quality is negatively associated in Malaysia. Overall, audit committee characteristics have a positive effect on firm performance. This study contributes to the literature as well as in empirical evidence on audit committee characteristics and firm audit quality. The results suggest that Big 4 firms have a negative impact on value based measure in Malaysia.